Профспілкове представництво у соціальному діалозі у сфері праці - Чанишева, Галина Іванівна; Чанышева, Галина Ивановна; Chanysheva, Galina (My University, 2011)
In the article the provisions of current legislation are being analyzed, including the Law of Ukraine «On the social dialog in Ukraine», and Draft of the Labour Code of Ukraine on the trade union's representation, and specific proposals on their improvement are being made.
Чанишева Г. І. Профспілкове представництво у соціальному діалозі у сфері праці / Г. І. Чанишева // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C.124-133.
Keywords: соціальний діалог; профспілки; профспілкове представництво; социальный диалог; профсоюзы; профсоюзное представительство; social dialogue; unions; union representation